Pelatihan Penelitian Tindakan Kelas (PTK) Bagi Guru Gunungkidul, D.I. Yogyakarta - Suyitno Suyitno (Universitas Muhammadiyah Purworejo, 2019)
One of the problems in developing teacher professionalism today is related to the problem of Classroom Action Research (CAR). The purpose of this activity is to provide training on writing Classroom Action Research (CAR). The training was attended by 25 teachers in Gunungkidul, Yogyakarta. The method used is 1) providing theoretical and practical knowledge about the integration of Classroom Action Research (CAR), 2) Providing material about data analysis and discussion in Classroom Action Research, 3) Viewing the responses of Classroom Action Research training participants.